Acute effects of three different stretching techniques on hamstring flexibility in professional football players - Erol, E.; Yildiz, R.; Yildiz, A.; Dogan, F. E.; Elbasan, B. (Baltic Journal of Health and Physical Activity, 2023)
Introduction: Hamstring injuries are common in physically active people and athletes. Lack of hamstring flexibility is the one of the most important characteristics of hamstring injuries in athletes. The aim of this study was to investigate effects of three different stretching techniques on hamstring flexibility in professional football players.